PENGARUH PENGELUARAN PEMERINTAH, DANA ALOKASI KHUSUS DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT - Mega Rosita, Ida Ayu Putu; Budhi, Made Kembar Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024, 2024)
This study aims to analyze the effect of government spending, special allocation funds and investment on economic growth and community welfare in the districts/cities of the province of Bali. The data used are data from 2011-2020. The data source in this study is secondary data, which was obtained from the Central Statistics Agency (BPS) of Bali Province. The analytical tool used in this research is path analysis using Partial Least Square (PLS) and SPSS software. The results of this study indicate that government spending has a positive and significant effect on economic growth. DAK has a negative and insignificant effect on economic growth. Investment has a positive and significant effect on economic growth. government spending has a positive and significant effect on the welfare of the community DAK has a positive and significant effect on the welfare of the community. Investment has no significant effect on people's welfare. Economic growth has a positive and significant impact on people's welfare. There is a significant positive indirect effect of government spending, DAK and investment on people's welfare through economic growth in districts/cities in Bali Province.